Trade-offs for the southern longline fishery in achieving a candidate South Pacific albacore target reference point - Skirtun, Maggie; Pilling, Graham M.; Reid, Chris; Hampton, John (Marine policy, 2019)
South Pacific albacore is a species of primary importance in the longline fishery of a number of Small Island Developing States in the Western and Central Pacific Ocean. Despite the fact that the stock is assessed as not being subject to overfishing and not overfished, economic returns have declined significantly over the past decade. This has led to calls for management intervention. Given stated biological and economic objectives for the fishery, members of the Pacific Islands Forum Fisheries Agency proposed an interim stock target reference point to the Western and Central Pacific Fisheries Commission that would imply a larger stock size, higher catch rates and a more profitable fishery (FFA Members, 2015). The purpose of this study is to examine the biological and economic consequences along the trajectories of two distinct longline effort reduction regimes that achieve the proposed target reference point within 20 years and review the trade-offs in terms of forgone catch or effort and forgone revenue. The two effort regimes examined are a one-off reduction implemented immediately, and a phased reduction under which effort is reduced by a fixed percent each year. The results are discussed in the light of wider Pacific Island objectives for fishery production and fleet profitability and highlights the importance of moving beyond a purely biological stock-based focus when providing management advice. •The South Pacific albacore stock is biologically healthy but fishery unprofitable.•Different effort reduction regimes yield different economic consequences.•Fast sharp effort reduction shown to generate higher rents than gradual cuts.•Management effort cut decision may consider wider objectives other than rents.